(2‐Pyridyl)sulfonyl Groups for ortho‐Directing Palladium‐ Catalyzed Carbon–Halogen Bond Formation at Functionalized Arenes. Issue 21 (19th October 2017) - Guilbaud, Johan; Labonde, Marine; Cattey, Hélène; Contal, Sylvie; Montalbetti, Christian; Pirio, Nadine; Roger, Julien; Hierso, Jean‐Cyrille
Abstract: We describe an efficient palladium‐catalyzed selective C–H ortho ‐monohalogenation (X=I, Br, Cl, F) of various functionalized (2‐pyridyl)arylsulfones. ortho‐, meta‐ and para ‐functionalization is tolerated at the arene group which undergoes C–H halogenation. Some modifications are also possible on the 2‐(arylsulfonyl)heteroaryl directing groups. A comparison of the halogenation efficiency suggests that bromination is the practical method of choice, while chlorination and fluorination are possible but more challenging. Under forcing conditions ortho ‐dihalogenation can also be achieved. Abstract :